The Effectiveness of Core Stability Exercise to Improve Functional Ability in A Lumbar Herniated Nucleus Pulposus Patient: A Case Study - Aditya Denny Pratama; Muhamad Elfitra Salam (Physical Therapy Journal of Indonesia, 2021)
Background: Hernia Nucleus Pulposus (HNP) is a condition in which the nucleus pulposus has bulged from the intervertebral disc, consequently damages the walls of the annulus fibrosus and compresses the nerves. Clinical problems such as radiating pain, sensory disturbances according to dermatomes, muscle weakness, restricted range of motion, especially during flexion, and decreased functional ability. Core stability exercise is one of the physiotherapy treatments to reduce pain and improve the patient's functional ability with lumbar HNP. The purpose of this study is to determine the effectiveness of core stability exercise on increasing functional ability in cases of lumbar HNP with Modified Oswestry Low Back Pain Disability Questionnaire as a parameter. Methods: A single case study provided a physiotherapy intervention to a 56-year-old female patient for four weeks with four evaluations. The dose of exercise given was three times a week, three sets, five repetitions, 6-9 minutes of each type of exercise, and hold time 5-10 seconds. The improvement of functional ability is measured by using the Modified Oswestry Low Back Pain Disability Questionnaire. Results: There was an improvement in functional ability as measured by Modified Oswestry Low Back Pain Disability Questionnaire. At pre-intervention, the Modified Oswestry score was 52% meaning the patient had severe disability. On the 4th week evaluation, the patient's Modified Oswestry score decreased to 26%, indicating moderate disability. Conclusion: This study showed that core stability exercise effectively improved functional ability in a patient with lumbar HNP.